CD25+ regulatory T cells transfer n‐3 long chain polyunsaturated fatty acids‐induced tolerance in mice allergic to cow's milk protein. Issue 12 (December 2013) - van den, L. W. J.; Meulenbroek, L. A. P. M.; van, B. C. A. M.; Hofman, G. A.; Boon, L.; Garssen, J.; Willemsen, L. E. M.
Abstract Background Recently, we have shown that dietary long‐chain n‐3 polyunsaturated fatty acids (n‐3 LCPUFA) largely prevent allergic sensitization in a murine model for cow's milk allergy. The aim of this study was to assess the contribution of regulatory T cells (Treg) in the prevention of food allergy by n‐3 LCPUFA. Methods C3H/HeOuJ female donor mice were fed a control or fish oil diet before and during oral sensitization with cow's milk protein whey. Acute allergic skin response (ASR), anaphylaxis, body temperature, serum immunoglobulins, and mouse mast cell protease‐1 (mmcp‐1) were assessed. Splenocytes of sham‐ or whey‐sensitized donor mice fed either control or fish oil diet were adoptively transferred to naïve recipient mice. Recipient mice received a whole splenocyte suspension, splenocytes ex vivo depleted of CD25+ cells, or MACS‐isolated CD4+ CD25+ Treg. Recipient mice were sham‐ or whey‐sensitized and fed control diet. Results The ASR as well as whey‐specific IgE and whey‐specific IgG1 levels were reduced in whey‐sensitized donor mice fed the fish oil diet as compared to the control diet. Splenocytes of control‐diet‐fed whey‐sensitized donors transferred immunologic memory. By contrast, splenocytes of fish‐oil‐fed whey‐sensitized – but not sham‐sensitized – donors transferred tolerance to recipients as shown by a reduction in ASR and serum mmcp‐1, and depletion of CD25+ Treg abrogated this. Transfer of CD25+ Treg confirmed the involvement of Treg in the suppression of allergic sensitization. Conclusions CD25+ Treg are crucial in whey allergy prevention by n‐3 LCPUFA.